Oxidative stress in maternal milk and cord blood in gestational diabetes mellitus: a prospective study - Fırat Erdoğan; Evrim Şenkal; Ömer Faruk Özer; İlke Özahi İpek; Şükriye Leyla Altuntaş; Şükriye Özde (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Reduced antioxidant defenses may reflect a poor protective response against oxidative stress and this may be implicated in progression of gestational diabetes mellitus (GDM). Oxidative stress induced by hyperglycemia plays a major role in micro and macrovascular complications, which imply endothelial dysfunction. OBJECTIVE: Our aim in this study was to investigate the association between GDM and oxidative stress markers measured in plasma, with regard to revealing changes to total antioxidant capacity (TAC) and total oxidant status (TOS) among mothers showing impairments in oral glucose tolerance tests (OGTTs). DESIGN AND SETTING: Prospective study at a university hospital in Turkey. METHODS: The study group consisted of 50 mothers with GDM, and 59 healthy mothers served as controls. Umbilical cord blood samples were taken from all mothers during delivery and breast milk samples on the fifth day after delivery. TAC, TOS, thiol and disulfide levels were measured. RESULTS: No statistically significant relationship between the blood and milk samples could be found. An analysis on correlations between TAC, TOS and certain parameters revealed that there were negative correlations between TOS and total thiol (r = -0.386; P < 0.001) and between TOS and disulfide (r = -0.388; P < 0.001) in milk in the control group. However, these findings were not observed in the study group. CONCLUSION: Our findings suggested that a compensatory mechanism of oxidative stress was expected to be present in gestational diabetes mellitus and that this might be ameliorated through good glycemic regulation and antioxidant supplementation.